2011
DOI: 10.1108/14636691111174261
|View full text |Cite
|
Sign up to set email alerts
|

Privacy by Design: an alternative to existing practice in safeguarding privacy

Abstract: PurposeThe purpose of this paper is to develop/elaborate the concept Privacy by Design (PbD) and to explore the validity of the PbD framework.Design/methodology/approachAttention for alternative concepts, such as PbD, which might offer surplus value in safeguarding privacy, is growing. Using PbD to design for privacy in ICT systems is still rather underexplored and requires substantial conceptual and empirical work to be done. The methodology includes conceptual analysis, empirical validation (focus groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Concerning privacy, the empirical findings support the findings of prior studies, showing that perceived privacy is a crucial factor that needs to be maintained (cf. Cavoukian, 2010;Van Lieshout et al, 2011) and constantly observed by responsible public servants. In summary, these four concepts possess good explanatory power of e-government portal acceptance, which shows a coefficient of determination of 0.661, and thus, a moderate to nearly substantial value (cf.…”
Section: Discussion Of Findings Implications and Limitationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Concerning privacy, the empirical findings support the findings of prior studies, showing that perceived privacy is a crucial factor that needs to be maintained (cf. Cavoukian, 2010;Van Lieshout et al, 2011) and constantly observed by responsible public servants. In summary, these four concepts possess good explanatory power of e-government portal acceptance, which shows a coefficient of determination of 0.661, and thus, a moderate to nearly substantial value (cf.…”
Section: Discussion Of Findings Implications and Limitationsmentioning
confidence: 97%
“…Moreover, privacy, ease of use, and usefulness aspects are the fundamental basis for each e-government undertaking, since available government services to citizens represent critical points of contact between public administrations and citizens (cf. Cavoukian, 2010;Sacco, 2007;Van Lieshout et al, 2011). In this context, responsible e-government officers should also keep in mind to evaluate if service access becomes designed in a search or exploration/discovery approach.…”
Section: Discussion Of Findings Implications and Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Security is also of significance within context of m-commerce and cloud, and this takes into account the development of mobile technology for enhancing usability and increasing security [22]. However, this may not always be possible due to implementation challenges, including a lack of economic incentives and a lack of acceptance by PbD end users in commerce [8,23]. In addition, the research highlights the following:…”
Section: M-commerce Cloud and Privacy: A Literature Reviewmentioning
confidence: 99%
“…Confidentiality and user privacy are important parts of PETs [46]. The combination must consider efficiency, usability, and privacy [23]. This is evident in the mobile agent security problem where greater emphasis is required on encryption [47].…”
Section: Industry Gaps and Challenges In Privacymentioning
confidence: 99%